2017
DOI: 10.1002/tox.22501
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and anti‐metastatic mechanisms of Rhizoma paridis saponins in Lewis mice

Abstract: Lung cancer is one of the most common causes of death in the world. Rhizoma paridis saponins (RPS) have been found to show inhibition of pulmonary adenoma in previous research. However, the detailed mechanisms of RPS from a holistic view have not been established. In this study, Lewis pulmonary adenoma mice were successfully established to analyze the pathways involved in RPS intervening tumor formation and progression. As a result, RPS inhibited levels of cytokines or receptors such as VEGFD, VEGFR3, RAGE, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Many cancer drugs can decrease MMP8 levels along with other MMPs: The plant-based isoflavones genistein and glycitein, as well as the flavone apigenin, down-regulate MMP8 expression in vitro and inhibit leukemia cell invasion [161,162] and decrease the viability of hepatocellular carcinoma cells [163]. Saponins from the plant Rhizoma paridis decreased the expression of inflammatory cytokines and MMP8 as well as reduced lung cancer tumor volume and growth in mice [164]. Therapeutic gold nanoparticles, which decreased ovarian cancer tumor growth and metastasis in vivo, also inhibited ovarian cancer cell proliferation, decreased MMP8 expression, and altered cytokine production in vitro [165].…”
Section: Resultsmentioning
confidence: 99%
“…Many cancer drugs can decrease MMP8 levels along with other MMPs: The plant-based isoflavones genistein and glycitein, as well as the flavone apigenin, down-regulate MMP8 expression in vitro and inhibit leukemia cell invasion [161,162] and decrease the viability of hepatocellular carcinoma cells [163]. Saponins from the plant Rhizoma paridis decreased the expression of inflammatory cytokines and MMP8 as well as reduced lung cancer tumor volume and growth in mice [164]. Therapeutic gold nanoparticles, which decreased ovarian cancer tumor growth and metastasis in vivo, also inhibited ovarian cancer cell proliferation, decreased MMP8 expression, and altered cytokine production in vitro [165].…”
Section: Resultsmentioning
confidence: 99%
“…To further verify the bio‐function of TAMs exosomes in vivo, we constructed OS xenograft model by subcutaneous injection and metastases model as reported 22–24 . TAMs exosomes were injected through tail vein every 7 days (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Rhizoma Paridis plays momentous roles in traditional Chinese medicine, and a large number of studies has confirmed that the main anticancer components of Rhizoma Paridis are steroidal saponins [ 21 , 22 ]. The steroidal saponins of Rhizoma Paridis have been demonstrated to induce cell cycle arrest, apoptotic cell death, and autophagy in human lung cancer cells [ 23 ].…”
Section: Discussionmentioning
confidence: 99%